Retrospective study of post term pregnancy and its outcome - Prajapati, Shetal; Chavda, Dolly (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Post Term Pregnancy is one of the commonest obstetric conditions. Pregnancy is called term when it lies between 37 weeks to 42 weeks (259 to 294 days) from the last menstrual period. If the pregnancy exceeds this period (above 42 completed weeks) it is classified as post term pregnancy. The overall incidence of post term pregnancy is 10.0% of all pregnancies. We estimate the recent incidence of post-date in Obstetrics and Gynecology Department, P. D. U. medical college, Rajkot (Gujarat). Methods: We are taking 500 cases of Post-date pregnancy (Retrospective cases) at P. D. U. Medical College, Rajkot (Gujarat) to know the method of induction, pregnancy outcome, maternal and Fetal complications. Results: In present study, out of 500 patients, induction was done in 366 patients and number of normal delivery was 377 (75.4%), LSCS was 113 (22.6%) and 10 (2%) was instrumental delivery. Conclusions: Post term pregnancies require early identification, effective and proper planned management. Rate of vaginal deliveries has increased due to effective Prostaglandins (PGs) and their easy availability.